A Novel Mobility Aid for the Blind through Ultrasound Pulsed Echo Modulated Nerve Stimulation - Fahad, M Shamiul; Khan, M Muwyid Uzzaman; Rabbani, K Siddique-e (Bangladesh Journal of Medical Physics, 2013)
There are no affordable and widely available technology based aid to give a blind person the power of free movement avoiding obstacles and dangers. Some ultrasound pulse echo based electronic aids deliver the information obtained through the echo through audio signals conveyed by means of ear phones, but these affect the capability of such an important sense organ which a blind person uses greatly to receive and discern information of the surroundings. In the present work this limitation is overcome by passing this information through nerve stimulations at a suitable point on the body, possible wrist. Here the delays of the received ultrasound echo-pulses are used to modulate the frequency of nerve stimulation, to give higher frequency for shorter distances. This was designed to match the common psychological response of attributing higher frequencies to danger, creating a natural reaction for moving away when an object is too close. The highest frequency a human nerve can be stimulated to is about 500Hz, and pulses with heights of 100V to 200V are required for stimulating nerves passing just under the skin using surface electrodes. Necessary electronic circuit design was developed and a prototype fabricated in the present work. The prototype was tested for short distances up to 20cm giving very good linear response between object distance and the stimulating frequency, with the inverse characteristics as mentioned above. Reduction of noise through proper housing and shielding will allow the device to be useful to a practical distance of about 10m using 40kHz ultrasound transducers. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14692 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 87-94